Práticas de gestão da qualidade em compras: estudos de caso em empresas automotivas - Oliveira, Adilson José Gomes de (Universidade Federal de São Carlos, 2020)
In the last decades with the advent of increasingly demanding consumers, quality has gained prominence among companies. For an organization to satisfy the customer's needs, it must use quality in its products and services, as it reflects the requirements necessary to meet those needs and exceed customer expectations. Starting from the point that quality management is an important competitive advantage, some authors argue that it has synergy with the purchasing area and attribute that the quality of raw materials and inputs greatly interfere with the quality of the final product, with the application of quality management practices in purchasing can bring enormous benefits to companies. The sector chosen for the research was the automobile industry, in view of the numbers that the sector presents in sales of motor vehicles and the great participation in the dissemination and application of new forms of management. From an exploratory bibliographic review, few studies were found in this area, highlighting the work of Sánchez-Rodriguez et al. (2005) and Hemsworth et al. (2008) who used a model called QMPP (Quality Management Practices Purchasing) for a quantitative study. The Sánchez-Rodriguez et al. (2005) served as a basis for listing the Quality Management in Purchasing practices explored in this work and the breakdown of these practices into operational elements was used to develop a semi-structured questionnaire that applied to three vehicle manufacturers served as an instrument for data collection . The evidence collected presented situations in which it is possible to establish the use of all the operational elements of a given practice, as well as some discrepancies in the use of these elements, concluding that the companies studied demonstrate the importance of the purchasing area being managed by the principles of quality .
Quality management practices in purchases: case studies in automotive companies
Keywords: Compras; Gestão de compras; Práticas de compras; Qualidade; Gestão da qualidade; Práticas da qualidade; Práticas da qualidade em compras; Purchasing; Purchasing management; Purchasing practices; Quality; Quality management; Quality practices; Quality practices in purchases; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO DA PRODUCAO; ENGENHARIAS::ENGENHARIA DE PRODUCAO::GERENCIA DE PRODUCAO